STUDY ON THE ENRICHMENT POTENTIAL OF VANADIUM-CONTAINING ORE FROM THE SIJJAK DEPOSIT (Лучшие интеллектуальные исследования, 2025)
Abstract: This study investigates the enrichment potential of vanadium-containing ore from the Sijjak deposit in Uzbekistan. The chemical, spectral, and scanning analyses of ore samples revealed a vanadium content ranging from 200 to 2500 g/t, with vanadium present mainly in oxidized form as V₂O₅. Gravity separation methods, including concentration table and jigging machine tests, were applied; however, the enrichment efficiency did not exceed 63%, and about 40% of vanadium remained in the tailings. Flotation was deemed impractical due to the low sulfide content of the ore. The findings suggest that direct leaching or pyrometallurgical processing may be more suitable for this type of ore, as further enrichment by traditional methods results in significant losses of the valuable metal.